Filogeografia de Pterodon emarginatus e Pterodon pubescens (Leguminosae) - Lima, Stefany Lorrayny (2019)
The species Pterodon emarginatus and P. pubescens, known as sucupira, occur in the Cerrado and have potential for medicinal and wood use. The comparative phylogeography of these species can help in understanding the historical pattern of distribution of genetic diversity, generating information for use and conservation. The objective of this work was to identify the phylogeographic structure of P. emarginatus and P. pubescens, and the comparative phylogeography of these species. The sample consisted of eleven populations for P. emarginatus and nineteen for P. pubescens, distributed in the states of Goiás, Tocantins, Bahia, Mato Grosso and Minas Gerais. The chloroplast regions sequenced were trnLE-trnLF and psbA-trnH, and the nuclear ribosomal was ITS101-102. In P. emarginatus, haplotypic and nucleotide diversity are high in chloroplast, as there is a high polymorphism in this region, with a high number of indels. The population structure is relatively low (FST = 0.10). In this species the populations Alvorada do Norte-GO, Cariri-TO, Luiz Eduardo Magalhães-BA and Monte Alegre de Goiás-GO stand out for genetic diversity and are located in an area of climate stability, influencing the evolutionary dynamics of the Cerrado. The dispersal has long distance potential (500 km). The demographic pattern has shown population growth for less than 150 a thousand years. In P. pubescens the haplotypic and nucleotide diversity are high in chloroplast and nucleus, with a high number of haplotypes. The population genetic structure is considerable (FST = 0.24), with a phylogeographic pattern marked by the divergence of populations of the Araguaia basin region, an area of influence on the Cerrado evolutionary dynamics, mainly Araguapaz-GO and Araguaiana-MT. Demographic history has shown population growth from 1.67 million years ago. Finally, P. emarginatus showed a higher diversity pattern in chloroplast, while in P. pubescens there was a high complexity of the phylogeographic pattern, and the population of Araguaiana-MT showed a high genetic distance. Despite the species separation, there is a highlight for populations that exhibit high haplotype sharing, mainly Araguaiana-MT and Araguapaz-GO. The species tree showed no distinction between species, corroborating the hypothesis of recent diversification. Comparative analysis of species suggests ancestral introgression or polymorphism, considering the high sharing of haplotypes. These species are possibly in the process of recent separation, and P. emarginatus is the species in the process of speciation.